Impact of Vascular Invasion of a Primary Tumor as a Strong Risk Factor for Disease Recurrence in Patients with Node-Positive Breast Cancer. Issue 5 (May 2015) - Fujii, Takaaki; Yajima, Reina; Morita, Hiroki; Hirakata, Tomoko; Miyamoto, Takeshi; Fujisawa, Tomomi; Tsutsumi, Soichi; Ynagita, Yasuhiro; Iijima, Misa; Kuwano, Hiroyuki
The presence of lymph node metastasis is considered to be the most significant indicator of prognosis. However, in some cases with node-positive breast cancer, cancer cell dissemination is localized to the lymphatic systems. It is, therefore, important to develop selection criteria for strong adjuvant therapy in patients with node-positive breast cancer. This study was undertaken to evaluate the presence of vascular invasion that may reflect systemic disease as a predictor of disease recurrence in node-positive breast cancer. We retrospectively evaluated the cases of 134 consecutive female patients with breast cancer with lymph node metastasis who underwent radical breast operations. We examined the relationship between recurrence and clinicopathological factors, particularly vascular invasion. The presence of vascular invasion was found to be significant in a univariate analysis. The presence of vascular invasion was the independent risk factor in a multivariate analysis. Among the 66 patients without vascular invasion, four (6.1%) had disease recurrence. On the other hand, among the 68 patients with vascular invasion, 15 (22.1%) had a recurrence. It is interesting to note that despite the presence of lymph node metastasis, the group without vascular invasion had few patients with distant metastases. Our results suggest that the presence of vascular invasion could be an indicator of high biological aggressiveness and may be a strong prognostic factor for node-positive breast cancer.